Use of a Team-Based Video Simulation to Complement a Lecture in Motivational Interviewing to Develop Students' Initial Attitudes and Skills - David F Malewski; Shane P Desselle; Ranjit Kali-Rai (University of Minnesota Libraries Publishing, 2021)
Background: Motivational interviewing (MI) is increasingly recognized for its patient-centered approach to clinician-patient communication and often effective in evoking appropriate changes in patient behavior.  Doctor of Pharmacy (PharmD) programs are increasingly incorporating MI education; however, doing so represents a challenge regarding availability of both time and labor capital. Case Description: This study reports on the use of a 90-minute software-based simulation and tutorial coupled with a 90-minute lecture in a 3-hour course session. In a subsequent session consisting of several brief interactions with standardized patients (SPs), students reflected upon their strengths and challenges as a result of attempting to apply the MI principles they learned during the educational intervention. Case Themes: Students' responses to a questionnaire delivered both before and after the simulation and lecture, showed improvements in several attitudinal components related to use of MI, as well as developing self-efficacies in deploying patient-centered communication strategies. A post-intervention survey without students' opportunity to study/prepare saw gains in student knowledge about MI. Case Impact: The measurements employed to determine student's attitude and knowledge showed good to very good internal consistency reliably based on calculated Cronbach's alpha and KR-20. Student reflections indicated their understanding of MI principles, even though they fell short of implementing them in large part during their encounters with SPs. Conclusion: Use of a video simulation undergone by teams of PharmD students coupled with a brief lecture might be an effective and efficient way of building a foundation for MI competency among PharmD students where instructors might lack labor capital and significant space in the curriculum.